Empowerment-Based Leadership in Transfer of Technology - Jerry Indrawan (The Republic of Indonesia Defense University, 2015)
The rapid development of global defence and security issues have brought about immense challenges for Indonesia. Improvement and development of the quality of Indonesia’s human resources within the defence area is imperative to answer such challenges. Self-sufficient defence industries (capability-based planning) in Indonesia has become the main concern of all related stakeholders in the country. Indonesia requires transfer of technology to develop its defence resources. Policies on transfer of technology are related to the capability of our leaders. Therefore, empowerment-based leadership is key to the transfer of technology policy. This paper will discuss the connections between empowerment-based leadership with transfer of technology policy as an effort to improve the quality of Indonesia’s human resources in the defence field.